A face‐to‐face comparison of the BBB cell models hCMEC/D3 and hBMEC for their applicability to adenoviral expression of transporters - Taggi, Valerio; Schäfer, Anima M.; Dolce, Asaél; Meyer zu Schwabedissen, Henriette E. (Journal of neurochemistry, 2024)
The blood–brain barrier (BBB) is a structure mainly formed by brain capillary endothelial cells (BCEC) whose role is to regulate the exchange of compounds between the blood and the brain. In this process efflux and uptake transporters play a key role. Aim of this study was to compare the two previously established cell lines hCMEC/D3 and hBMEC as BBB cell models for the application of an adenoviral system to transiently express OATP2B1 and Pgp. Comparison of hCMEC/D3 and hBMEC mRNA and protein levels of BBB markers showed a unique expression pattern for each cell line. While showing similar expression of the efflux transporter BCRP, transferrin receptor (TFRC) and of the tight junctions proteins Occludin and ZO‐1, hCMEC/D3 displayed higher levels of the endothelial marker PECAM1, VE‐cadherin, Von Willebrand Factor (VWF) and of the efflux transporter Pgp. Moreover, measuring integrity of the monolayer by determining the Trans‐Endothelial Electrical Resistance (TEER), electrical capacitance (CCl), and inulin apparent permeability coefficient (Papp) revealed higher TEER and lower CCl for hBMEC but comparable Papp in the two cell lines. Following adenoviral infection, enhanced OATP2B1 and Pgp expression and functionality could be observed only in hBMEC. Importantly, the adenoviral expression system did not affect expression of BBB markers and permeability in both cell lines. Taken together, our results provide first evidence that hBMEC is an applicable human BBB cell model in which adenoviral infection can be used to transiently express and investigate transporters of interest. hCMEC/D3 and hBMEC are two previously established Blood–Brain Barrier (BBB) cell models. Our study compared the two cell lines for the expression of key markers, tight junctions and transporters of the BBB, revealing different expression patterns in the two cell lines. Furthermore, we assessed the applicability of the two cell lines for transient overexpression of OATP2B1 and Pgp dependent on adenoviral infection, showing increased expression and functionality only in hBMEC. Collectively, our data suggests that hBMEC is a human BBB cell model suitable for transient expression and study of relevant transporters.